Analysis of Language Errors at the Level of Phonology and Morphology in Exposition Texts by High School Students - Prasetyo, Dzaky Ramzy; Sulistyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study investigates the morphological errors made by students of SMA Negeri 1 Bulu, Sukoharjo, in their exposition texts. By cataloguing common mistakes—such as inappropriate vocabulary choice, unclear sentence constructions, and incorrect compound word formations—the research aims to highlight how a deeper understanding of morphology can aid students in identifying and correcting these linguistic issues. Methodology: Adopting a descriptive qualitative design, the study analyzed 18–24 student‐written exposition texts collected from tenth‐ grade classes. Researchers served as key instruments, employing observations, interviews, and document analysis to gather data. The analytic process proceeded through systematic stages of data collection, identification, classification, and thematic analysis, culminating in drawing evidence‐based conclusions about error patterns. Results: Findings reveal that student writings frequently contain morphological lapses, underscoring gaps in their understanding of word formation and modification. The prevalence of these errors demonstrates the critical need for explicit morphology instruction as part of Indonesian language teaching. Applications/Originality/Value: By pinpointing specific morphological challenges, this research provides practical tools for both teachers and learners to diagnose and remedy linguistic errors. The study offers a novel contribution to language‐error research in Indonesian education, presenting targeted recommendations for curriculum designers to integrate morphology‐focused exercises that enhance students’ writing proficiency and overall language awareness.